Wastewater reuse in agriculture and health in Vietnam - Hung Nguyen-Viet; Phuc Pham Duc (Michigan State University and UNESCO, 2019)
The study provides a framework to estimate the health risk of farmers using wastewater in agriculture. The study addresses the SDG 6.3: to contribute to inform water recycling and reuse. Exposure to wastewater via contact with Nhue River water, pond water and composted excreta represents an important health risk. Study results are useful in developing an integrated strategy for risk management in the agricultural settings.